DIVERSITY OF INDIGENOUS LAYERS IN COMPARISON WITH EXOTICS IN JORDAN - Raed M. Al-Atiyat (Journal of Animal and Plant Sciences, 2013)
Genetic variation of a hundred indigenous layers chicken and its genetic relatedness to twenty exotic layers chickens of each Pakistani chicken and commercial layers were assessed in Jordan using six microsatellite markers. the microsatellite markers showed an average allele number of 5.8 per locus, expected heterozygosity of 55.8% and high polymorphism of 54% in Jordan indigenous chicken. on the other hand, the genetic relatedness between the three breeds, that were originally independent, was described by pairwise genetic distance. the genetic distance was the shortest (0.135) between indigenous chicken and Pakistani chicken, revealing indigenous chicken was more closely related to Pakistani layer chicken than the commercial layers. this result confirmed the historical information about their common origin. long genetic distance (0.205) was showed between indigenous chicken and commercial layers. this might be a result of gene flow by crossing individuals of both sometimes ago. finally, the longest genetic distance (0.288) was found between commercial layers and Pakistani chicken. the overall results are valuable for sustainable genetic conservation program to reserve indigenous Jordan layer chicken for its unique genetic sources.
Keywords: Indigenous and Exotic layers; Genetic diversity and distances; Microsatellite markers